TINJAUAN AKUSTIK PERANCANGAN INTERIOR GEDUNG PERTUNJUKAN - Dwi Retno Sri Ambarwati (FBS UNY, 2009)
Many factors must be considered in the planning of the acoustic ofinterior auditorium according to its function, so that the performance of theartists or actors can be caught better and the quality of the show is able to satisfythe audience. Especial conditions that must be fulfilled in the planning of theacoustic of interior auditorium are: enough loudness by shortening the distanceof the audience with the sound, heightening the source of sound, theaccompaniment of the floor, encircle the source of sound by the voice reflector,the dimension of room must match with the space volume, avoiding parallelsound reflector and locate the audiences in the beneficial area. Other conditionsare the right form of space, energy of sound distribute into whole space, free fromthe handicaps of acoustic and the form treatment of floor, wall and plafond andalso veneering them with the sound absorber material. Financial considerationusually represent the constrictor of the acoustic repair, because getting a goodquality of acoustic cost a lot of money .Keyword: acoustics, auditorium, and interior building